Bloodstream infection among children presenting to a general hospital outpatient clinic in urban Nepal - Pradhan, R; Shrestha, U; Gautam, S; Thorson, S; Shrestha, K; Yadav, B; Kelly, D; Adhikari, N; Pollard, A; Murdoch, DR (Public Library of Science, 2012)
BACKGROUND: There are limited data on the etiology and characteristics of bloodstream infections in children presenting in hospital outpatient settings in South Asia. Previous studies in Nepal have highlighted the importance of murine typhus as a cause of febrile illness in adults and enteric fever as a leading bacterial cause of fever among children admitted to hospital. METHODS: We prospectively studied a total of 1084 febrile children aged between 2 months and 14 years presenting to a general hospital outpatient department in Kathmandu Valley, Nepal, over two study periods (summer and winter). Blood from all patients was tested by conventional culture and by real-time PCR for Rickettsia typhi. RESULTS: Putative etiological agents for fever were identified in 164 (15%) patients. Salmonella enterica serovar Typhi (S. Typhi) was identified in 107 (10%), S. enterica serovar Paratyphi A (S. Paratyphi) in 30 (3%), Streptococcus pneumoniae in 6 (0.6%), S. enterica serovar Typhimurium in 2 (0.2%), Haemophilus influenzae type b in 1 (0.1%), and Escherichia coli in 1 (0.1%) patient. S. Typhi was the most common organism isolated from blood during both summer and winter. Twenty-two (2%) patients were PCR positive for R. typhi. No significant demographic, clinical and laboratory features distinguished culture positive enteric fever and murine typhus. CONCLUSIONS: Salmonella infections are the leading cause of bloodstream infection among pediatric outpatients with fever in Kathmandu Valley. Extension of immunization programs against invasive bacterial disease to include the agents of enteric fever and pneumococcus could improve the health of children in Nepal.